Folha rota, de Machado de Assis: Mulheres livres e pobres na ordem patriarcal - Da Conceição Silva, Eliane [UNESP] (Universidade Estadual de Maringa, 2009)
This article analyzes the short story Folha rota (1878) by Machado de Assis, taking to account the transformation process of the patriarchy, bearing in mind it's decadence within the increasing urbanization context through 19th century. From the representation of female characters and their everyday's life in the narrative, we discuss the violence experienced by free and poor women involved in the inherent power relations in that society. In this perspective, we intend to indicate an interpretation of literary work as an important device of social criticism, as much as, to give a contribution to an accurate comprehension of Machado de Assis's work, especially his short stories.
Folha rota: Free and poor women within patriarchal order
Keywords: Machado de Assis; Patriarchy; Violence; Woman situation